The incremental information content of replacement cost earnings - Beaver, William H.; Griffin, Paul A.; Landsman, Wayne R. (Journal of Accounting and Economics, 1982)
The study explores the incremental explanatory power of replacement cost earnings variables (derived from ASR 190 data) with respect to explaining cross sectional differences in security returns. As such, the study is a natural extension of previous research, including analyses of the effect of security returns of ASR 190 data at the time of disclosure, investigations of cross sectional relationships between security returns and historical cost earnings, and studies of multiple signals. The basic finding is that pre-holding gain net income provides no incremental explanatory powerm given knowledge of historical cost earnings. However, the converse does not hold. Taken together, the findings are consistent with the contention that pre-holding gain net income is a garbled version of historical cost earnings. The basic finding is robust under several extensions of the initial research design. The research design incorporates a two-stage approach which permits a determination of the incremental explanatory power of collinear variables. The findings are in contrast to those of a previous study by Easman et al. (1979). The nature of the difference in research design inducing the difference is identified. Potential reasons for the difference in findings are provided.